2012
DOI: 10.4103/0974-9233.97939
|View full text |Cite
|
Sign up to set email alerts
|

Olive-harvesting eye injuries

Abstract: Purpose:To document the types of ocular trauma that occurs during the olive-harvesting season in a region of the Middle East.Materials and Methods:Ophthalmic assessments of all patients were performed by one ophthalmologist. Examinations included visual acuity, slit-lamp evaluation of the anterior segment, intraocular pressure measurement and posterior segment assessment after pupil dilatation.Results:The study cohort comprised 119 patients who presented for ocular injury due to olive harvesting. Seven patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, differing outcomes were achieved in patients with laser-induced corneal injury. While Stojanovic et al (2003) observed a prophylactic effect against haze development after PRK by oral ascorbic acid, Yulish et al (2012) reported a null effect, in addition to the perioperative MMC (Stojanovic et al, 2003;Yulish et al, 2012). This suggests that the treatment effect may depend on the disease etiology and the underlying mechanisms of how ascorbate modifies corneal haze in different conditions need to be further investigated.…”
Section: Vitamin Cmentioning
confidence: 99%
“…However, differing outcomes were achieved in patients with laser-induced corneal injury. While Stojanovic et al (2003) observed a prophylactic effect against haze development after PRK by oral ascorbic acid, Yulish et al (2012) reported a null effect, in addition to the perioperative MMC (Stojanovic et al, 2003;Yulish et al, 2012). This suggests that the treatment effect may depend on the disease etiology and the underlying mechanisms of how ascorbate modifies corneal haze in different conditions need to be further investigated.…”
Section: Vitamin Cmentioning
confidence: 99%
“…Agricultural eye injuries have been studied with various crops such as citrus,[ 8 ] olive[ 9 ] and cocca. [ 10 ] Nevertheless, date palm tree eye injuries have not been studied in detail except for few case reports.…”
Section: Introductionmentioning
confidence: 99%